Etiology of Traumatic Causes of Extensor Pollicis Longus Tendon Rupture: A Systematic Review - Alsaedi, Obaid Faisal; Alshahir, Alwaleed Abdullah; Alzahim, Ammar Faisal; Alharbi, Waleed Mousa; Alsaygh, Ehab Fayez; Alhamaid, Yousef Ahmed; Alahmadi, Hussam Mohammed; Beek, Asem Saleh; Elgarya, Ibrahim Mohamed (Journal of Hand and Microsurgery, 2023)
Introduction The extensor pollicis longus (EPL) is a muscle that follows a complex anatomical course in the hand to allow for thumb extension. Almost all manual activities require the use of the EPL; therefore, when ruptured it can be very disabling for patients. The etiologies behind traumatic EPL rupture were mostly attributed to distal radius fracture in the literature. However, EPL rupture remains uncommon, and other traumatic etiologies exist. Therefore, this systematic review aimed to provide a holistic view of the traumatic etiologies behind the EPL rupture and fill the global lack of knowledge regarding this rare injury.Materials and Methods We searched among Cochrane Central Register of Controlled Trials (CENTRAL) Embase, Medline, and Cochrane Database of systematic review register databases via Ovid, with no restriction on the date, including studies containing data about the etiology of traumatic causes of EPL tendon rupture with available full text, and excluding non-English and animal studies.Results A total of 37 articles with 371 cases constituted the basis of this review. We classified the etiology of the EPL rupture into three groups according to the affected anatomical structure that caused the EPL rupture (fracture-related, soft tissue-related, and mallet thumb).Conclusion Distal radius fractures remain the most common cause of EPL rupture; however, other causes, such as lacerations, blunt trauma, and direct cuts to the EPL tendon, should be considered.
Keywords: EPL rupture; mallet thumb; tendon rupture; trauma